Use of antihypertensive medication before diagnosis of atrial fibrillation in Finland – results from the nationwide FinACAF -study. (14th October 2021) - Luojus, A; Halminen, O; Mustonen, P; Putaala, J; Haukka, J; Linna, M; Itainen-Stromberg, S; Tiili, P; Kinnunen, J; Niiranen, J; Hartikainen, J; Niemi, M; et al.
Abstract: Background and aims: Long-standing arterial hypertension increases the risk of cardiovascular morbidity including atrial fibrillation (AF), coronary heart disease and renal failure. Arterial hypertension is the most common aetiologic factor associated with the development of AF and is also the most prevalent co-morbid cardiovascular disease in patients with AF. Coexisting arterial hypertension together with AF increases further the risk of stroke, heart failure and overall mortality. The Finnish AntiCoagulation in Atrial Fibrillation (FinACAF) -study is a nationwide retrospective register-based AF study that combines data from several Finnish health care registers. In this sub-study, we characterized the use of antihypertensive medications in patients with new-onset AF. Methods: This sub-study included all adult new-onset AF patients of the FinACAF study from January 2007 to December 2018. Patients were excluded if they were under 18 years of age, had any oral anticoagulant purchase in the year prior to AF diagnosis, or had diagnosis of AF or warfarin purchases between the years 2004–2006. Appropriate data such as anonymized study ID's, ICD-10 diagnoses, and drug purchases (dates, ATC-codes, amounts) were obtained from the National Prescription Register as well as the Finnish Hospital and Primary care registers. The antihypertensive medication purchases from the year preceding the AF diagnosis were analysed and identified by appropriate ATC-codes. Purchases one-month prior to the new-onset AF diagnosis were excluded from in order to avoid confounding by any medication changes due to AF diagnosis. Results: Of 229, 282 patients with new-onset AF 164, 527 (71.8%) had purchased antihypertensive medication during the year prior to the AF diagnosis. The most common antihypertensive drugs used were beta blockers (n=108, 510; 47.3%), ACE-inhibitors or angiotensin receptor blockers (n=104, 840; 45.7%), diuretics (n=79, 270; 34.6%) and selective calcium channel blockers (n=61, 610; 26.9%). Diltiazem was purchased by 2, 001 patients (0.9%) and verapamil by 1, 508 patients (0.7%). At the beginning of the study period, beta-blockers were the most widely used antihypertensive agents, but between 2007 and 2018, RAAS-inhibitors (ACE inhibitors and ARB blockers) became the most widely used group of antihypertensive drugs (Figure 1). Conclusion: Most Finnish new-onset AF patients had at least one pre-existing antihypertensive medication in use before the diagnosis of AF. Beta blockers were the most common antihypertensives until the latest years when RAAS-inhibitors became the most prescribed antihypertensive agents, whereas the use of diltiazem and verapamil was marginal in the treatment of hypertension before the AF diagnosis. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Helsinki and Uusimaa Hospital District research fundThe Finnish Foundation for Cardiovascular Research